Correlation between Serum Visfatin Level with Glycemic Control in Type 2 Diabetes Mellitus Subjects - Fadillah, Ismirayanti; Nurahmi, Nurahmi; Kurniawan, Liong Boy (Indonesian Association of Clinical Pathologist and Medical laboratory, 2025)
Visfatin is an endocrine, paracrine, and autocrine peptide that functions in cell proliferation and glucose metabolism. Visfatin has insulin-like characteristics. Serum visfatin level is increased in diabetes mellitus subjects despite other contradicting results. The study aimed to investigate the correlation between serum visfatin level and glycemic control in subjects with type 2 diabetes mellitus. The study was a cross-sectional involving all patients diagnosed with type 2 diabetes mellitus at Dr. Wahidin Sudirohusodo Hospital as the research population. The research sample was all patients with type 2 diabetes mellitus and had HbA1c examination results that met the inclusion criteria. The level of serum visfatin was measured using the ELISA technique from Biobase. Data were statistically analyzed using Kolmogorov-Smirnov test, Mann-Whitney test, and Spearman’s correlation test. The research sample consisted of 70 subjects who were grouped into good glycemic control and poor glycemic control based on HbA1c values. Serum level of visfatin did not significantly differ between those with good and poor glycemic control (0.54±0.58 vs. 0.51±0.45 ng/mL, p=0.990). The level of serum visfatin and HbA1c value did not significantly correlate (p=0.813).